Impact of Human Resource Management Practices on the Job Satisfaction of Employees in the Textile Industry - Kaushal, Robin; Singla, Meenu (Nepalese Journal of Management Science and Research, 2023)
The significant role of human resources creates a necessity for organizations to formulate and develop the human resource management practices in the best interest of the employees. It is observed that human resource management practices pose significant impact on the job satisfaction and retention of talented employees in the industry. HRM practices proclaimed as a system that attracts, develops, motivates, and retains employees to ensure the effective implementation and the survival of the organization. The present paper is undertaken to study the perception of employees in the selected textile units of Punjab. The paper is an attempt to document the impact of different human resource management practices on the job satisfaction of employees in the textile industry and to find influential HRM practices as per the perception of the employees. It further examines the influence of human resource practices on the job satisfaction of employees. The results showed that Compensation and Promotion, Organizational Culture, Selection and Training, Performance Appraisal, Grievance redressal and Support and Development are the major HRM practices that leads to job satisfaction in textile industry.